IMPULSIVITAS DAN AGILITAS PADA REMAJA YANG ORANGTUANYA BERCERAI - Sri Hajarwati Ningsi; Asniar Khumas; Kurniati Zainuddin (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACTThe inner conflicts resulting from divorce don’t cause all adolescents to behave negatively. There are some adolescents who continue to behave positively and are able to learn from the bad experiences of their parents, but there are also adolescents who behave negatively which leads to impulsivity. This qualitative research uses a case study which aims to describe impulsivity and agility in adolescents whose parents are divorced and the factors that influence it. The number of respondents was six adolescent girls whose parent’s divorced and six significant others from the respondents. Data were collected using interview techniques. Based on the results of the study, it’s known that the forms of impulsivity found include smoking, self-harm, talking abusive to friends, skipping college and always imagining things to self-injury. This is influenced by three factors, such as personality, family and social environment (peers and school). Meanwhile, the forms of agility that were found included respondents busy themselves with organizational and community activities, working at school and not being afraid to build relationships. This is influenced by two factors, such as situational and personality. This research can contribute knowledge in developmental psychology and family psychology.Keywords: Adolescents, Agility, Divorce, Impulsivity ABSTRAKKonflik batin yang diakibatkan perceraian tidak membuat semua remaja berperilaku negatif. Ada beberapa remaja tetap berperilaku positif dan mampu belajar dari pengalaman buruk orangtuanya, tetapi ada juga remaja yang berperilaku negatif mengarah pada perilaku impulsivitas. Penelitian kualitatif ini menggunakan studi kasus yang bertujuan untuk mendeskripsikan impulsivitas dan agilitas pada remaja yang orangtuanya bercerai serta faktor-faktor yang mempengaruhinya. Jumlah responden sebanyak enam remaja perempuan yang orangtuanya bercerai dan enam significant others dari responden. Data dikumpulkan menggunakan teknik wawancara. Berdasarkan hasil penelitian diketahui bahwa bentuk impulsivitas yang ditemukan meliputi perilaku merokok, memukuli diri, berbicara kasar pada teman, bolos kuliah, dan selalu membayangkan hal-hal untuk bunuh diri. Hal ini dipengaruhi oleh tiga faktor, yaitu kepribadian, lingkungan keluarga, dan lingkungan sosial (teman sebaya, sekolah). Sedangkan bentuk agilitas yang ditemukan meliputi responden menyibukkan diri pada kegiatan organisasi dan komunitas, sekolah sambil bekerja serta tidak takut untuk menjalin hubungan. Hal ini dipengaruhi oleh dua faktor, yaitu situasional dan kepribadian. Penelitian ini dapat memberi sumbangsih ilmu dalam psikologi perkembangan dan psikologi keluarga.Kata kunci: Agilitas, Impulsivitas, Perceraian, Remaja